Life satisfaction and its relationship to optimism, social support, and religiosity among a sample of female breast cancer survivors in Kuwait - Alrasheed, Malak (Jordan Journal of Social Sciences, 2020)
The study aimed to detect the level of life satisfaction among a purposive sample of Kuwaiti female survivors of breast cancer in light of some of the social, psychological and demographic variables. The sample consisted of (217) outpatients of a cancer treatment center who completed a questionnaire consisted of demographic data, Optimism scale, and life satisfaction scale. The results showed: high social support and religious levels among respondents, medium levels of optimism and life satisfaction, statistically significant correlations between levels of social support and religiosity, and levels of optimism and life satisfaction, a statistically significant difference on life satisfaction based on levels of economic status, and not social or job status. The analysis of regression equation model of life satisfaction showed that optimism, social support, and educational level were the most important explanatory factors. Results were interpreted in light of previous studies and cultural factors, and study concluded with recommendations.